Modulating ADAM-10 activity and expression in cervical and oesophageal cancer cells - Wagiet, Mateen (Division of Medical Biochemistry, 2017)
The ADAMs (A Disintegrin And Metalloproteinase) is a family of transmembrane and secreted proteins essential in cellular fate determination, wound healing, cell migration, proliferation and angiogenesis. Previous studies have linked a range of ADAMs, which include ADAM10 to cancer development and progression. Research in our laboratory found endogenous ADAM10 levels to be higher in both oesophageal and cervical cancer cell lines. Reports in the literature have highlighted a correlation between high levels of ADAM10 expression with that of cancer cell biology; hence ADAM10 shows promise as an anti-cancer target. The aim of this study was to modulate ADAM10 activity in oesophageal and cervical cancer cell lines using the small molecule inhibitor GI254023X as well as previously undescribed two molecules generated en route to synthesizing GI254023X, namely SN-254 and SN-311. A CX₃CL1 ELISA functional assay as an indicator of ADAM10 activity showed a decrease in CX₃CL1 cleavage after treatment with GI254023X, SN-311 and SN-254 suggesting that all three compounds substantially inhibited ADAM10 activity. The effects of these compounds on the cell biology of WHCO5 oesophageal and HeLa cervical cancer cells were monitored. Our data shows that GI254023X, SN-254 and SN-311 inhibit oesophageal and cervical cancer cell proliferation, and cause cell death via apoptosis as observed by PARP cleavage, and elevated Caspase 3/7 activity. Drug treatment also resulted in an increase in cellular adhesion as well as a significant decrease in the invasion and migration of WHC05 and HeLa cells. The effect of ADAM10 inhibition on typical markers of the epithelial to mesenchymal transition state was also examined. An increase in epithelial cell markers (E-Cadherin, B-Catenin) and a decrease in mesenchymal marker expression (Vimentin) post treatment with the compounds tested strongly suggested that ADAM10 plays a role in mesenchymal cell transition. These results suggest that ADAM10 activity is necessary for the biological phenotypes that associate with cervical and oesophageal cancer cells and that targeting ADAM10 with inhibitors have potential as anticancer therapies.